THE PORTRAIT OF YUSUF IN ULUGBEK KHAMDAM’S NOVEL “BALANCE” - Kalandarova Dilafruz Abdujamilovna; Orifjonova Ozoda Dilshodovna (The Conference Hub, 2025)
This article reveals the social situation of society through the life of Yusuf, the main character of Ulugbek Khamdam’s novel “Balance”, the hero’s thoughts, and his efforts to survive.
Keywords: Ulugbek Khamdam, new century literature, society, balance, internal struggle, interest, norm, materiality, spirituality.